Intake Planning in Loma River, Tolikara Regency - Helen Gianditha Wayangkau; Amaliah Azis; Alfian Adie Chandra; David David; Davy I. Robert Jansen (Jurnal Indonesia Sosial Teknologi, 2024)
The provision of clean water in Karubaga City has been hampered by inadequate piping distribution networks, forcing reliance on drilled wells in villages. This study aims to address the problem of inadequate clean water facilities by planning an effective water intake system for the Loma River in Tolikara Regency. Using a combination of quantitative and qualitative methods, the research analyzed hydrological data, intake hydraulics, and the structural stability of intake buildings. Results indicate that the Loma Intake requires significant rehabilitation due to sediment deposition, while the Palagi Intake needs an evaluation of the pipeline network to improve flow pressure and distribution. The study concludes that redesigning and constructing efficient water intake systems is crucial to meeting the community's clean water needs while mitigating health risks from water pollution.